OECD Work on Future Educational Environments - Theisens, Henno (OECD Publishing, 2008)
Designing school buildings to respond to change is not a new idea. But perhaps what is different today is the kind and degree of change which we have to anticipate. The OECD is carrying out projects that can help in the planning and design of future educational facilities - exploring trends in education and studying innovative learning environments. Education planners have long grappled with the type of change connected with demography, for example changing local patterns in the number of school places needed over a period of time. But new challenges lie in the complexity and uncertainty which are characteristic of the 21st century world. The findings of the OECD's project "Schooling for Tomorrow: Trends Shaping Education" show some sources of this uncertainty, including falling birth rates, increasing economic globalisation and growing numbers of single parent families.
Keywords: Education